IMPLEMENTATION OF ACCOUNTABILITY AND TRANSPARENCY IN PUBLIC SERVICE (Case Study at IRD RSUD Dr. Saiful Anwar) - Ira Ardella Putri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Management of public sector organization (especially government organization) still has many problems in the administration of public service field. It is caused by a good governance which has not been applied yet. In the effort to realize the good governance, the implementation of the principles such as the principle of accountability and transparency is very important. The purpose of this research is to investigate the implementation of the principles contained in the good governance, especially the principles of accountability and transparency in public Health service at IRD RSUD Dr. Saiful Anwar Malang. The method used is a descriptive method with qualitative approach. Techniques for collecting data are by using questionnaires, interviews, observation and study of literature. Through the research which was conducted at IRD RSUD Dr. Saiful Anwar, it is found that some indicators contained in the principles of accountability and transparency have already been well implemented there.Key Words: Public Service, Accountability, Transparency